Pengaruh Alokasi Pajak Antar Periode, Pertumbuhan Laba, dan Good Corporate Governance terhadap Kualitas Laba - Handayani, Yunita; Astutie, Yanti Puji (Majors Accounting, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2021)
Influence of Inter-Period Tax Allocation, Profit Growth, Managerial Ownership and Independent Commissioner on Profit Quality in Energy Sector Companies listed on the Indonesia Stock Exchange in 2017-2020).This study aims to test the Effect of Inter-Period Tax Allocation, Profit Growth, Managerial Ownership and Independent Commissioner on Profit Quality in Energy Sector Companies listed on the Indonesia Stock Exchange in 2017-2020).This type of research method is quantitative research using a descriptive approach. The data used in this study is secondary data. The population in this study are all energy sector companies listed on the Indonesian stock exchange from 2017 to 2020. The sample uses a purposive sampling technique, namely selecting samples with certain criteria, so that the sample in this study is 33 data from 13 energy sector companies listed on the Stock Exchange. Indonesian effect. Data was collected by using documentation techniques and literature study. The data analysis technique used in this research is using multiple linear regression analysis and moderated regression analysis using SPSS statistical data processing software.The results of this study indicate that the inter-period tax allocation, profit growth, managerial ownership and independent commissioners partially have no effect on earnings quality, but simultaneously the inter-period tax allocation, profit growth, managerial ownership, and independent commissioners affect earnings quality.